Single Nucleotide Polymorphism SNP Analysis ‎of Exon6Follistatin Gene Relatedtopolycystic ‎Ovarian Syndrome inThiQar Governorate‏.‏ (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
Follistatin has been identifiedas a nominee gene for polycystic ovary syndrome (PCOS) from relationship studies.Acting to control the developmentof ovarian follicles and as an antagonist to aromatase action, changes in Follistatinrole or expression may affect main features of PCOS alteration.The aim of the recent study was to study the association of FST gene to define if genomicdifferencesarerelated with phenotypic structures of PCOS patients in a case–control suggestion study.Methods:This study involved 30 women with PCOS and 20 healthy women, whowerematched by their ageand anthropometric and biochemical profiles.The study was designed to examine theseparation of deoxyribonucleic acid (DNA), and genotype analysis was done for all the study participants using PCR-SNP.Results:Polymorphisms (SNPs) in the exon 6 FST gene region were determined for PCOS patients and controls, it was found that PCOS patientshad17 SNP in different samples, and after performing amino acid sequences alignment for these SNPs, it was observed that the last two SNPs of sample C12 constituted a non-synonym mutation, and the functional conformation of the produced FST gene weremodified with regard to exon 6 in the genotype C12. When this exonic SNP appears in the three-dimensional structure of the resulting proteins of C12 genotypes, the positively charged amino acid, Asp, is converted into another positively charged amino acid, His, in position 331 of the whole amino acid sequence of FST protein.The conclusionis that this, in turn doesn’t change the final phenotypic manifestation of the protein, and there was no alteration in the phenotypes of the PCOS patients.